(untitled) (American Journal of Islam and Society, 1999)
The book is an edited collection of papers, the majority of which were presented at a conference organized in 1994 by the Chr Michelsen Institute in Bergen, Norway, under the title Construction of Gender Relations in Processes of Modernisation: Women and Islamisation. It is divided into seven chapters and an introduction. Generally, the book attempts to comprehend so-called “religious fundamentalism”; specifically, it examines Islamic fundamentalism. It endeavors to “analyze the ways in which Muslim women develop distinct voices and participate in Islamization processes,” thus setting new agendas and redefining their role in society. Since the majority of the researchers are “outsiders” (outside Islam), the editors emphasize two points that are of crucial importance for the credibility of the work. First, unlike most Western studies on gender and Islam, this one claims to be conducted with sincere and good intentions, with an effort to distance itself from Western prejudices that so often portray Muslim “women’s relation to Islam as being universally its victims.” Second, this study considers cultural backgrounds, education, class, and age to consideration and assess Muslim women in their various national settings - once again in contrast to the usual Western studies that tend to lump Muslim women together into one category. Hence the ethnographic cases presented in the book represent a broad spectnun of Muslim women’s religious activities, ranging from Senegal in the West to Iran in the East. The different case studies center on Muslim women’s engagement in public religious activities, because it is this involvement which is expected to forge their new role away from the fixed traditional patriarchal one. However, their role in the discourse of Islamization does not necessarily address the overall issue of gender relations; rather, it offers a new alternative and questions the supremacy of Western feminism as the ultimate answer to gender equality. In chapter one, titled “Feminist Reinterpretation of Islamic Sources: Muslim Feminist Theology in the Light of the Christian Tradition of Feminist Thought,” Roald discusses the development of the so-called “Muslim feminist tradition,” particularly the attempts by some Muslim women to re-interpret the Islamic sources from a female perspective. She focuses on the intellectual ...